Sustainable Organic Waste Solutions: Maggot Cultivation Training and Community Engagement in Bresela Village - Supartha, Anak Agung Ayu Rika Putri; Kumaradewi M, Ni Putu Dhanan (Society : Jurnal Pengabdian Masyarakat, 2026)
Organic waste management remains a major challenge in rural areas, including Bresela Village, Bali, which is predominantly characterized by household and agricultural activities. The high volume of organic waste that has not been optimally managed highlights the need for an applicative and sustainable community-based waste management approach. This community service program aims to enhance community understanding, skills, and participation in organic waste management through training and mentoring on maggot cultivation. The method employed is a descriptive qualitative approach using observation, interviews, and hands-on practice. The activity was conducted on November 15 in a one-day program consisting of problem observation, field studies through training and demonstration of maggot cultivation, and evaluation of the activity outcomes. The results indicate an improvement in community understanding of organic waste management and a shift in perception toward viewing waste as a valuable resource.